2003
DOI: 10.1093/ajcn/78.6.1141
|View full text |Cite
|
Sign up to set email alerts
|

Variability of measured resting metabolic rate

Abstract: Repeated morning and evening measurements of RMR were stable and highly correlated. Day-to-day measurements of RMR were not significantly different. RMR measured in the afternoon after a 4-h fast and exercise was approximately 100 kcal/d higher than RMR measured in the morning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(80 citation statements)
references
References 19 publications
0
75
0
5
Order By: Relevance
“…A study comparing the area under the curve of RMR above baseline measures over 6 h documented a total caloric increase from a 1200-kcal meal of 80-90 kcal (Kinabo & Durnin, 1990;Haugen et al, 2003). The percentage of kcal burned during the fourth and fifth hour are 22 and 9%, respectively (Reed & Hill, 1996), suggesting a limited increase above true RMR by measurement after a 4-h fast.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study comparing the area under the curve of RMR above baseline measures over 6 h documented a total caloric increase from a 1200-kcal meal of 80-90 kcal (Kinabo & Durnin, 1990;Haugen et al, 2003). The percentage of kcal burned during the fourth and fifth hour are 22 and 9%, respectively (Reed & Hill, 1996), suggesting a limited increase above true RMR by measurement after a 4-h fast.…”
Section: Discussionmentioning
confidence: 99%
“…A 7-min (Schols et al, 1992), a 10-min (Igawa et al, 2002), and a 25-min (Kashiwazaki et al, 1990) rest have been tested with no significant difference in RMR afterward. A protocol using a 30 min rest for the morning measure but a 15 min rest in the afternoon (Haugen et al, 2003) found o100 kcal difference in RMR, a difference that may have reflected the combined effects of rest time and length of fasting (12 vs 4 h). Thus the 15 min rest time employed in the current study was likely not a source of measurement error.…”
Section: Discussionmentioning
confidence: 99%
“…Resting energy expenditure was measured using the ventilated-hood technique [35]. Criteria for a valid resting energy expenditure were: a minimum of 15 min of steady state and no food intake for at least 4 h before the measurement.…”
Section: Methodsmentioning
confidence: 99%
“…Dessa forma, baseando-se nos pressupostos de que as equações preditivas propostas até então não têm oferecido satisfatório nível de concordância; que a variação dos vieses de estimativa é de considerável magnitude em diferentes populações; e que as intervenções em programas de controle do peso corporal são facilitadas quando o equilíbrio energético é realizado mediante a identificação dos valores da TMB 17 , o objetivo do presente estudo foi comparar as medidas da TMB obtidas mediante recursos de calorimetria indireta com medidas estimadas por intermédio das equações preconizadas pela World Health Organization e pelo Henry & Rees 12 em uma amostra de universitários, na tentativa de apontar novos direcionamentos para a predição da TMB.…”
Section: N T R O D U ç ã Ounclassified
“…Outros estudos coletaram dados por 60 minutos, desconsiderando os 20 minutos iniciais 25 ou selecionando o período de tempo de maior estabilidade dos dados, resultando em um tempo de coleta maior ou menor de acordo com a variabilidade observada 26 . Assumindo que a variabilidade da medida da TMB possa ser estabelecida por fatores biológicos, instrumentos de medida e viés de medida, e que os viéses de medida incluem o erro técnico do avaliador e as variações quanto à adaptação dos avaliados aos equipamentos de medida 17 , parece razoável assumir que esses fatores possam explicar a acentuada variabilidade dos valores individuais encontrados no presente estudo. Não obstante, quantificar a contribuição desses vieses na medida da TMB torna-se uma tarefa difícil visto a subjetividade desses fatores.…”
Section: I S C U S S ã Ounclassified